THE DUALISM OF COURTS’ ABSOLUTE JURISDICTION OVER LAWSUITS CONCERNING THE IMPLEMENTATION OF TAXPAYER DETENTION: BETWEEN THE DISTRICT COURT AND THE TAX COURT - Reynalda Reynalda; Immanuela Yolanda (JCH (Jurnal Cendekia Hukum), 2025)
Detention (gijzeling) of a tax obligor is a coercive administrative measure regulated under Law No. 19 of 2000, which amends Law No. 19 of 1997 on Tax Collection by Distress Warrant (PPSP Law). The regulation of absolute jurisdiction over lawsuits concerning the implementation of detention has resulted in dualism between the District Court and the Tax Court. This study analyses the regulation of exclusive jurisdiction over lawsuits related to the implementation of tax obligor detention, based on legislative provisions and judicial practice. The method consists of normative legal analysis using legislative and analytical approaches, along with case studies of court decisions. The findings indicate a normative discrepancy between Article 34(3) of the PPSP Law, which refers to the District Court, and Article 31(2) and Article 33 of the Tax Court Law, along with Article 50 of the General Court Law, which tend to place disputes over the implementation of tax collection, including detention, within the jurisdiction of the Tax Court. Additionally, inconsistencies in judicial interpretation are evident in practice. By applying the ratio legis approach and the principles of lex posterior derogat legi priori, lex specialis derogat legi generali, and lex specialis systematis, the Tax Court is more appropriately designated as the competent forum. Therefore, harmonisation of regulations is necessary to ensure legal certainty and protect taxpayers’ rights.